Innovation of Sombu Corn as a Modernized Traditional Cuisine of Manggarai Regency - Paur, Yohana Spayolin Sarina; Payong, Polikarpus; Firnalastri, Emiliana; Maka, Marianus Aldrik; Jebarut, Agustinus (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research aims to innovate the processing of local foods, addressing the decline of traditional foods due to the rise of foreign fast foods. The study emphasizes the importance of preserving traditional foods, such as Sombu, a corn-based dish from Manggarai Regency, and demonstrates how modernization can help these foods compete in today's market. Method: The research employed a combination of Brainstorming sessions, business management strategies, and techniques for making, processing, and marketing traditional foods. The study involved selecting specific locations and subjects for service to ensure targeted and effective interventions. Practical Applications: The findings highlight the potential for local food innovations to rejuvenate traditional culinary practices, making them competitive with foreign alternatives. This research opens opportunities for young people, especially students, to engage in creative and profitable culinary innovations, thereby sustaining cultural heritage and stimulating economic growth. Conclusion: The study successfully showcased new innovations in local food processing, resulting in modernized traditional foods that can compete with international products. These innovations not only preserve cultural heritage but also motivate the younger generation to contribute to creative and profitable culinary practices.